Viabilidade de implantação de certificação LEED –Categoria energia e atmosfera em uma agroindústria do oeste do Paraná - Bertolini, Daniele (2020)
Energy policies around the world are increasingly focused on efficiency and the economy produced by supplying the various sectors of society. Environmental certifications arose in order to contribute to the mitigation of environmental impacts generated by projects, from the design, construction, renovation and expansion phases, operation and maintenance of these buildings. The agribusiness market is a major consumer of energy around the world and, also in Brazil, however, it is a strategic sector economically and in constant growth and promising expansion. This work carries out an analysis of sustainability criteria based on the Leadership in Energy and Environmental Design (LEED) certification for existing buildings (LEED O + M), when verifying the feasibility of implantation in an agroindustry in the food sector, in western Paraná . The methodology consisted of verifying the attributions required for the Energy and Atmosphere category, a prerequisite for Energy Efficiency Management Practices, which addresses the level 1 Walk-through energy audit; with five items met, the survey identified the identification of efficiency measures that require additional studies and estimate the reduction in consumption and building costs. Adequate levels of environmental comfort were also presented, the evaluation indicated a percentile of 78.43 for the mild mesothermic climatic zone and 64.29 for NBR 15220 and NR 17. The results were satisfactory to what was proposed, being assertive in saying that for this industry it is able to meet the mandatory prerequisite; Energy Efficiency Management Practices established within the Energy and Atmosphere Dimension of the LEED O + M category.